Trait and Factor Counseling to Improve Career Planning Skills of Junior High School Students - Ni Komang Anggun Melati Saputra; Ni Ketut Suarni; I Ketut Gading (Bisma The Journal of Counseling, 2025)
Career planning skills are an individual's ability to take steps toward achieving all goals in preparing for the future, which is done well in advance for long-term purposes. This study aims to determine whether Trait and Factor counseling services are effective in improving career planning skills among students at junior high school. This study employs a quasi-experimental design. The method used is a nonequivalent control group design. Measurements in this study were conducted twice through pretest and posttest. The research subjects consisted of 164 male students and 136 female students. Data collection methods in this study were conducted through interviews, questionnaires, and observations. After data from all respondents or data sources were collected, data analysis was conducted using inferential statistical analysis. Based on the results of the data analysis, the study found that Trait and Factor counseling is effective in improving career planning skills among eighth-grade students, as evidenced by the results of the pretest and posttest. The findings of this study can assist guidance counselors and educational institutions in designing more effective, systematic, and developmentally appropriate career guidance services for adolescent students.